Korelasi antara Kuat Tekan Bebas dengan Kuat Tekan Geser langsung pada Tanah Lanau Disubstitusi dengan Pasir - Sudarman, Aulia R; Afriani, Lusmeilia; Iswan, Iswan (Universitas Lampung, 2016)
This study aims to get the correlation between the soil compressive strength and soil shearstrength directly on silt substituted with granulated materials. This is done because if buildingstructures on the silt soil will cause several problems including a small value of the compressivestrength and low shear strength after incurring. For the testing is done with a mixture of sand, siltsoil so that it can be seen how much sand mixture to resist the forces on the load that is above theground.To determine the sand effect on silt soil , with the compressive strength and shear strength that hasbeen made by way of mixing the sand by 10%, 20%, 30% and 40%. From the test results showedan increase in the compressive strength of 0.3723 kg/cm 2 in a mixture of 10% sand and a decreasein the mixture thereafter. In the direct shear strength value increased 30% when variations mixtureof sand that is equal to 0.4290 kg / cm 2 , the cohesion of 0.27 kg / cm 2 and the friction angle in at26.170.Keywords: silt soil, sand, soil compressive strength, soil direct shear